KEBEBASAN BERAGAMA DI SMU SELAMAT PAGI INDONESIA KOTA BATU MALANG - Umi Sumbulah (AL-TAHRIR, 2014)
This study attempts to examine the implementation of religious freedom in a multicultural education institution, namely at SMU Selamat Pagi Indonesia (SMU-SPI )in Batu City, East Java. This study focuses on the meaning of religious freedom for the academic community, and the supporting and hindering factors for the implementation of religious freedom in this school which has diverse multicultural backgrounds. This empirical study uses a qualitative- phenomenological approach. It shows some important findings. First, the meaning of religious freedom for the academic community of this school is the freedom for everyone to practice their religion in accordance with the religion and beliefs of each, while respecting the religion and beliefs of others. Second, the application of freedom of religion in this school is expressed through moral conducts amongst the school community such as compassion, good advice, moral support, religious commitment and respect for other religious observance. In addition, the implementation of religious freedom is also evident in the efforts of the school to provide teachers and spiritual guide to students in accordance to their respective religion and in the establishment of places of worship for all religions.